Importance Evaluation of Power Grid Transmission Lines Based on Multidimensional Information Feature Mapping - Keji Chen; Yingqi Tie; Maohua Li (Energies)
The importance evaluation of power grid transmission lines is crucial for preventing catastrophic grid failures, enhancing grid resilience, and ensuring the safe and stable operation of the power system. To address the limitations in existing transmission line evaluation methods, such as reliance on single evaluation metrics, insufficient consideration of information transmission between adjacent lines, and the impact of line failures on system load loss, this paper proposes a comprehensive evaluation method based on multidimensional information feature mapping. First, evaluation metrics are established from three dimensions—power transmission characteristics, grid network structure, and resilience improvement—each reflecting the importance of transmission lines from different perspectives. Then, a hybrid weighting method is introduced, combining subjective and objective weights through a game theory approach to calculate the comprehensive weights, enabling the multidimensional information-based importance evaluation of transmission lines. Finally, an improved network efficiency index, representing the current operational performance of the grid, is developed to validate the proposed evaluation method. A simulation analysis using the IEEE-39 bus test system verifies the feasibility and accuracy of the proposed approach.